Acting for a Reason and Following a Principle - McAninch, Andrew James (Ethical theory and moral practice, 2015)
According to an influential view of practical reason and rational agency, a person acts for a reason only if she recognizes some consideration to be a reason, where this recognition motivates her to act. I call this requirement the guidance condition on acting for a reason. Despite its intuitive appeal, the guidance condition appears to generate a vicious regress. At least one proponent of the guidance condition, Christine M. Korsgaard, is sensitive to this regress worry, and her appeal in recent work to the constitutive principles of action can be seen, in part, as a response to it. I argue, however, that if we are to appeal to the constitutive principles of action to resolve the regress, then we must determine whether acting on such principles is also subject to the guidance condition. This raises a dilemma. If following these principles is subject to the guidance condition, then the regress remains unresolved. But if not, then the rationale for applying it to acting for a reason vanishes as well. I conclude that we should embrace an account of acting for a reason that rejects the guidance condition.